P8 A freely available, simple-to-use, computational model of atherosclerosis. (5th April 2020) - Watterson, Steven; Parton, Andrew; McGilligan, Victoria; Chemaly, Melody; O'Kane, Maurice
Abstract : Motivation: Atherosclerosis is the leading causes of death globally, but is challenging to study in vivo or in vitro due to the logistical and ethical challenges involved. A computational model has the potential to transform our ability to study the disease by being quick, simple and consistent to work with at no financial or ethical cost. However, no detailed, openly-available computational models exist. Clinical studies hint that pharmaceutical therapy may be possible. Here, we develop the first detailed, computational model of atherosclerosis to be built to systems biology standards and use it to develop multi-drug therapeutic hypotheses. Results: We assembled high quality network maps and models describing atheroma development from the literature. Maps and mathematical models were produced using the Systems Biology Graphical Notation (SBGN) and Systems Biology Markup Language (SBML), respectively, and the model was constrained against laboratory and clinical data. We identified five drugs that potentially reverse advanced atheroma formation when acting in combination. Availability and Implementation: The map is available from our publications in the Systems Biology Graphnical Notation Markup Language (SBGN-ML) file format. The model is available in the from the BioModels repository and from our publications, in SBML file format.